THE CORRELATION BETWEEN RETINAL NERVE FIBRE LAYER THICKNESS, OPTIC NERVE HEAD PARAMETER, AND RELATED RISK FACTOR IN GLAUCOMA PATIENT - Wardhana, Arif Kusuma; Ekantini, Retno; Gani, Tatang Talka; Jati, Krisna Dwi Purnomo (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction and Objective: To investigate the correlation between retinal nerve fibre layer (RNFL) thickness and the past RNFL thickness, related risk factor (gender, age, myopia, intraocular pressure (IOP), blood pressure). And RNFL parameter (symmetricity and four quadrants RNFL thickness) and optic nerve head parameter (rim area and vertical cup disc ratio) Methods: 39 right eyes of both sex and various age underwent examination including IOP measurement, subjective refraction for determining refractive error, and optical coherence tomography (OCT) for RNFL and ONH analysis. The follow up were done after one year. Result: The RNFL symmetricity, superior, nasal, inferior, temporal RNFL thickness showed significance correlation with RNFL thickness (R= 0.487, p= 0.002), (R= 0.915, R= 0.749, R= 0.897, R= 0.702 with p= <0.001), but not showed significance correlation with rim area and vertical cup disc ratio (R= 0.175, p= 0.286) and (R= -0.093, p= 0.574). A significance correlation also showed with increasing age, gender, and systolic blood pressure (R= -0.387, p= 0.015), (R= 0.441, p= 0.005) and (R= -0.418, p= 0.008). But not showed significance correlation with history of past RNFL thickness, refractive error, IOP, and diastolic blood pressure (R= 0.258, p= 0.113), (R= 0.005, p= 0.975), (R= -0.234, p=0.152), and (R= 0.060, p=0.717). Conclusion: RNFL thickness measurements showed significance correlation with RNFL parameter. It is not clear if past RNFL thickness, refractive error and IOP related with RNFL thickness even showed significance correlation with age, gender, and systolic blood pressure. Keywords: Glaucoma, RNFL thickness, optical coherence tomography, optic nerve head